Cover. (March 2017) - Gomez‐Lopez, Nardhy; Romero, Roberto; Leng, Yaozhu; Garcia‐Flores, Valeria; Xu, Yi; Miller, Derek; Hassan, Sonia S.
Abstract : Front cover : The image is based on the Original article, Neutrophil Extracellular Traps in Acute Chorioamnionitis: A Mechanism of Host Defense, by NARDHY GOMEZ‐LOPEZ et al., DOI:10.1111/aji.12617 .